2022
DOI: 10.3390/rs14236105
|View full text |Cite
|
Sign up to set email alerts
|

A Sentinel-2 Based Multi-Temporal Monitoring Framework for Wind and Bark Beetle Detection and Damage Mapping

Abstract: The occurrence of extreme windstorms and increasing heat and drought events induced by climate change leads to severe damage and stress in coniferous forests, making trees more vulnerable to spruce bark beetle infestations. The combination of abiotic and biotic disturbances in forests can cause drastic environmental and economic losses. The first step to containing such damage is establishing a monitoring framework for the early detection of vulnerable plots and distinguishing the cause of forest damage at sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The selection of VIs was based on their sensitivity in detecting various vegetation properties. For example, Typical VIs are well known for assessing photosynthetic activity, forest health status, and detecting forest stressors such as pest outbreaks [43,55,59,[97][98][99][100]. On the other hand, Water VIs primarily provide a quantitative measure of water content in various tree species, early detection of water stress, and assessment of drought impacts on forested areas [48,55,56,61,[100][101][102][103].…”
Section: Evaluation Of VI Sensitivity In Detecting and Predicting Dro...mentioning
confidence: 99%
“…The selection of VIs was based on their sensitivity in detecting various vegetation properties. For example, Typical VIs are well known for assessing photosynthetic activity, forest health status, and detecting forest stressors such as pest outbreaks [43,55,59,[97][98][99][100]. On the other hand, Water VIs primarily provide a quantitative measure of water content in various tree species, early detection of water stress, and assessment of drought impacts on forested areas [48,55,56,61,[100][101][102][103].…”
Section: Evaluation Of VI Sensitivity In Detecting and Predicting Dro...mentioning
confidence: 99%
“…In Table 3, we would like to update the references in Column number 5. Thus, Table 3 will be updated from the following: [39] Disease Water Stress Index DSWI NIR−GREEN SWIR1+RED [54] Normalised Multi-band Drought Index NMDI NIR−(SWIR1−SWIR2) NIR+(SWIR1−SWIR2) [51] Typical VIs Normalized Difference Vegetation Index NDVI NIR−RED NIR+RED [105] Enhanced Vegetation Index EVI To the following: [39] Disease Water Stress Index DSWI NIR−GREEN SWIR1+RED [58] Normalised Multi-band Drought Index NMDI NIR−(SWIR1−SWIR2) NIR+(SWIR1−SWIR2) [55] Typical VIs Normalized Difference Vegetation Index NDVI NIR−RED NIR+RED [108] Enhanced Vegetation Index EVI 2.5*(NIR−RED) NIR+6*RED−7.5*BLUE+1 [109] Soil-Adjusted Vegetation Index SAVI NIR−RED (NIR+RED+1)*1.5 [110] Transformed Vegetation Index TVI 2 NIR−RED (NIR+RED)+0.5 [46] TC components In Section 4, Subsections 4.1-4.4, all the references were updated from the following:…”
Section: Evaluation Of VI Sensitivity In Detecting and Predicting Dro...mentioning
confidence: 99%
“…Therefore, the non-invasive approach and efficiency of VIs in forest health monitoring, which is made possible using high temporal frequency and spatially explicit satellite data, can provide insights into current and future forest health status over largescale forested areas. For example, various VIs have been applied in forest health monitoring, and the most common ones are the Normalized Difference Vegetation Index (NDVI), the Soil-Adjusted Vegetation Index (SAVI), the Transformed Vegetation Index (TVI), the Normalized Difference Moisture Index (NDMI), the Disease Water Stress Index (DSWI), Tasseled Cap Wetness (TCW), and Tasseled Cap Greenness (TCG) [38,39,[45][46][47][48]50,[53][54][55][56]. Despite their high accuracy, other conventional methods require constant, time-consuming, and cost-ineffective monitoring service, thus indicating the utter importance and innovativeness of remote sensing-produced VIs in monitoring forest health status over large-scale forested areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Huo, Persson and Lindberg [32] demonstrated that the Ratio Drought Index (RDI) and Normalised Difference Water Index (NDWI) using SWIR bands showed more prominent differences between healthy and stressed samples (green-attack). Candotti, et al [47] found that the vegetation indices that used the Red-Edge (B06 and B07), SWIR (B12), and Red (B04) bands were more appropriate for effectively differentiating between healthy and stressed (red-attack) trees. Similar to this study, NDVI was the most reliable index in the Bryk, et al [48] study, using a thresholding mask for deadwood, and might be helpful for spruce forest monitoring by Landsat8 imagery on a landscape scale.…”
Section: Effectiveness Of Dead Spruce Separation By Sentinel-2-based ...mentioning
confidence: 99%